Correspondence of physical activity and fruit/vegetable consumption among prostate cancer survivors and their spouses. (26th March 2015) - Myers Virtue, S.; Manne, S.L.; Kashy, D.; Heckman, C.J.; Zaider, T.; Kissane, D.W.; Kim, I.; Lee, D.; Olekson, G.
<x xml:space="preserve">Abstract</x> A healthy diet and physical activity are recommended for prostate cancer survivors. Interdependence theory suggests that the spousal relationship influences those health behaviours and the degree of correspondence may be an indicator of this influence. This study evaluated the correspondence between prostate cancer survivors and spouses regarding physical activity and fruit/vegetable consumption. Baseline data from an ongoing randomised control trial were utilised. Men who had been treated for prostate cancer within the past year and their partners (N = 132 couples) completed self‐report measures of physical activity, fruit/vegetable consumption, relationship satisfaction and support for partner's healthy diet and physical activity. Couples reported similar fruit/vegetable consumption and physical activity as indicated by high levels of correspondence. Greater fruit/vegetable correspondence was related to higher relationship satisfaction (F = 4.14, P = 0.018) and greater patient (F = 13.29, P < 0.001) and spouse‐rated support (F = 7.2, P < 0.001). Greater physical activity correspondence was related to greater patient (F = 3.57, P = 0.028) and spouse‐rated support (F = 4.59, P = 0.031). Prostate cancer survivors and spouses may influence each other's diet and exercise behaviours. Couple‐based interventions may promote healthy behaviours among this population.